Beyond the Screen: A Creative Exploration of Content that Engages on YouTube Discussed by Social Media Influencers - Cristina Munaro, Ana; Cristine Francisco Maffezzolli, Eliane; Santos Rodrigues, João Pedro; Cabrera Paraiso, Emerson (Review of Business Management, 2024)
Purpose – The study aims to investigate the most popular content discussed by social media influencers on YouTube and its associated valence, to delineate the content categories favored by top Brazilian influencers, and to assess their impact on consumer digital engagement. Theoretical framework – This study draws upon influencer marketing, social media influencer (SMI) literature, and digital engagement. Design/methodology/approach – A data mining approach was used. The methodology includes the collection of video post characteristics, engagement metrics, and audio transcriptions from 34,563 videos on 103 YouTube channels. After textual preprocessing, a topic modeling stage is performed using the Latent Dirichlet Allocation (LDA) algorithm and sentiment analysis. Findings – The study identified 19 critical dimensions of video content on YouTube. The top 3 content categories with the highest user digital engagement are: Family, Entertainment/General, and Culture & Entertainment. The sentiment analysis shows that content about Beauty, Gastronomy, and Economics, Entrepreneurship & Business have the highest proportional positive valence. Politics, Economy & News, Entertainment/General, and Gaming have high percentages of negative valence. Practical & social implications of research – The results provide a deep understanding of YouTube's popular content and digital engagement rates. This is essential for companies and SMIs looking to maximize their reach, resonate with their target audience, and stay competitive in the dynamic digital landscape. It allows for more effective communication, content creation, and strategic decision-making. Originality/value – Understanding the content on YouTube can provide valuable insights for businesses, marketers, and content creators to optimize their communication strategies.